Role of Efflux Pumps in the in vitro Development of Ciprofloxacin Resistance in Listeria monocytogenes - Jiang, Xiaobing; Yu, Tao; Xu, Ping; Xu, Xiaobo; Ji, Shengdong; Gao, Wujun; Shi, Lei (Frontiers in Microbiology, 2018)
Efflux is a primary fluoroquinolone resistance mechanism in Listeria monocytogenes. In the present study, ciprofloxacin resistant strains were selected by exposure of sensitive strain to progressively increasing concentrations of ciprofloxacin and then the roles of efflux pumps Lde and MdrL in the development of resistance to ciprofloxacin were also investigated in L. monocytogenes. Ciprofloxacin sensitive strain of L. monocytogenes exhibited reduced susceptibility to this antibiotic after induction. Cross-resistance to ethidium bromide (EtBr) was observed in ciprofloxacin-induced strains. However, cross-resistance to benzalkonium chloride (BC) did not occur in this study. Compared to the wild-type strain HL06, the expression levels of lde were increased in four ciprofloxacin-induced strains. The single-gene deletion mutants of lde and mdrL from the ciprofloxacin-induced resistant strain HL06CIP4 were constructed. However, decreased minimum inhibitory concentration (MIC) of ciprofloxacin was observed only in HL06CIP4Δlde compared to that of the parental strain HL06CIP4. Ciprofloxacin uptake appeared to be obviously increased in HL06CIP4Δlde in relative to HL06CIP4. These evidences suggested that efflux pump Lde is involved in ciprofloxacin resistance in L. monocytogenes HL06CIP4. The deletion of lexA had no effect on the expression levels of lde in HL06CIP4 in the absence or presence of ciprofloxacin, indicating that LexA was not involved in the regulation of efflux pump Lde in L. monocytogenes.